PENERAPAN TIPE PEMBELAJARAN TEAM GAMES TOURNAMENT DENGAN MEMANFAATKAN MEDIA QUIZIZZ UNTUK MENUMBUHKAN MOTIVASI BELAJAR SISWA - Pramita, Chika Vindi; Sudibyo, Elok (Program Studi S1 Pendidikan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This study aims to determine the motivation level of students when TGT type cooperative learning is applied by using Quizizz digital games media. This study used a one group posttest only design. The data collection technique consists of a questionnaire method and an observation method to measure the level of student motivation and is supported by the interview method. The results of this study indicate that from the results of questionnaires and observations obtained a very high level of student learning motivation. However, the interview results show that this learning is more suitable if used as innovative learning in learning assessment. The conclusion of this research is that the TGT type of learning has an effect in fostering student learning motivation and it is recommended that supporting learning is needed before the tournament to support students to gain knowledge about the material to be tournamentized.